Green synthesis of water dispersied graphene nanosheets using gamma radiation and natural capping agents. (December 2018) - Abd El-Rehim, Hassan A.; Tartour, Ahmed R.
Abstract: Clean and green reduction of graphene oxide (GO) to graphene (GR) nanosheets was achieved by gamma irradiation. The reduction efficiency was evaluated using UV–vis spectra. The effects of gas atmosphere, pH value of the dispersion medium, type of capping agent and absorbed dose on GR nanosheet formation were studied. Sodium carboxymethyl cellulose, ethyl hydroxyethyl cellulose, glucose and polyvinyl alcohol were investigated as capping agents. The presence of such one of them was proven to be crucial. The GR nanosheets obtained were characterized using AFM, TEM, FTIR, XRD, TGA and DSC. Effectiveness, simplicity, reproducibility, and low energy consumption are the merits of this technique. Highlights: Water dispersied graphene nanosheet/s were prepared using Gamma irradiation. A colloidal dispersion of GR was obtained when capping agent natural polymers were used. Effects of pH value, capping agent type and absorbed dose on GR formation were studied. The GR nanosheets were characterized using AFM, TEM, FTIR, and XRD.